Certain sufficient conditions for φ -like functions in a parabolic region - KAUR, Hardeep; BRAR, Richa; BILLING, Sukhwinder Singh (Studia Universitatis Babeș-Bolyai Mathematica, 2023)
To obtain the main result of the present paper we use the technique of differential subordination. As special cases of our main result, we obtain sufficient conditions for \(f\in A\) to be φ -like, starlike and close-to-convex in a parabolic region. Mathematics Subject Classification (2010): 30C80, 30C45. Received 21 May 2020; Accepted 21 July 2020.